Pengukuran Reksadana Menggunakan Sharpe dan Treynor Model Jenis Pasar Uang, Pendapatan Tetap dan Saham - Hutagalung David Ferdinan; Eko A. Widyanto; Burhanuddin Burhanuddin (Jurnal Indonesia Sosial Sains, 2022)
The Purpose of this research determine the results of measuring the performance of each type of mutual funds, namely the type of Money Market, Fixed Income and stocks in 2016 - 2020, if using the Sharpe method and the Treynor method and finding the type of Mutual fund with the best performance from these measurements. Sampling technique in this study using purposive sampling technique, totaling 30 samples of mutual funds. The analytical tool used in performance measurement is Microsoft Excel. The result of this performance measurement is the performance measurement of money market mutual funds, resulting in the Sucorinvest Money Market fund with the best performance based on Sharpe and Treynor methods. Fixed income mutual funds with Danamas Stabil that have the best performance based on Sharpe measurements and from stock funds, there are 2 Mutual funds, namely Sucorinvest Equity Fund and Sucorinvest Maxi Fund. The results of these measurements are Danamas Stabil from fixed income mutual funds are able to have the best performance of the 3 types of mutual funds based on Sharpe measurement, while based on the Treynor method, produce money market funds that have the best performance.